Geological mapping of the inner shelf off Cape Town's Atlantic Seaboard, South Africa - Van Zyl, Frederik Wilhelm (Department of Geological Sciences, 2019)
The Atlantic Seaboard is an 18 km stretch of coastline located on the Cape Peninsula, South Africa, roughly between the Cape Town suburbs of Mouille Point in the north and Hout Bay in the south. It borders heavy shipping traffic and contains a mix of urban and natural environments including up-market seaside neighbourhoods and is part of the Table Mountain National Park. The predominantly rocky coastline has a northeast–southwest orientation with interspersed sandy pocket beaches. A narrow, low-lying coastal plain (marine terrace) in the north merges with coastal cliffs further south. The geomorphology and sedimentology of the coast are closely linked to the underlying geology, influencing the shape of coastal embayments and promontories, as well as the composition and distribution of sediment. Hydrographic, geophysical and sedimentological techniques were used to collect high-resolution bathymetry, seafloor geology and sediment distribution data to better understand modern coastal processes. The results indicate a low-relief seafloor consisting of Malmesbury Group rocks in the north. To the south the seafloor consists of high-relief Cape Granite reefs interspersed with fine to medium grain sand and bioclastic (shelly) gravel. Sediment transport is generally northward by longshore drift. In the south, the high-relief granite reef and headlands form sediment traps resulting in several large pocket beaches and offshore sediment deposits. In the north, the low-relief Malmesbury bedrock is largely free of sediment, except within narrow erosional gullies. Most sediment rapidly passes through to the north resulting in a sediment-starved rocky seafloor. The three principal sources of beach sand are aeolian fine sand transported by the Karbonkelberg headlands bypass dune entering the sea at Sandy Bay, biogenic carbonate production along the coast, and weathering of Table Mountain Group sandstone and granite bedrock. A fourth source is sediment entering the system via longshore drift from the south of Duiker Point. The water depth around the Duiker Point headland is presently too deep for sediment to be transported easily through longshore drift, other than during large storm events, but during past sea-level low stands this would have played an important part in supplying sediment to the coast. Changes in sea level play an important part in shaping the geomorphology of the coastline. Beach deposits, both sandy and boulder beaches have been left at various elevations along the coast, both offshore and onshore. Although today the Sea Point area is protected by sea walls and man-made structures, a higher sea level was responsible for shaping the narrow coastal plain. Increasing rates of global sea-level change are becoming an important issue all over the world and the Atlantic Seaboard coast is not immune to the effects of sea-level rise. The frequency and magnitude of storm events that breach the sea defences erode beaches and sea cliffs and cause damage to private and public property are likely to increase in the future